2017
DOI: 10.1647/2016-204
|View full text |Cite
|
Sign up to set email alerts
|

Serratospiculosis in Captive Peregrine Falcons (Falco peregrinus) in Switzerland

Abstract: Infection with Serratospiculum species was identified in a captive peregrine falcon (Falco peregrinus) in Switzerland. Pathologic and parasitologic examination results revealed generalized severe granulomatous airsacculitis, with intralesional adults, larvae, and eggs of Serratospiculum species. Subsequently, an individual coprological analysis of the remaining 15 falcons (peregrine falcons and gyrfalcons [Falco rusticolus]) from the same owner was performed. Eggs of Serratospiculum species (4 birds) and Capil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In our study, despite retrieving only two helminths, the peregrine falcon presented signs of respiratory illness including wheezing upon auscultation of the air sacs as well as thickening and opacity of the affected air sac. Veiga et al (2017) showed that adult Serratospiculum species can survive for many years within the air sacs causing alterations in the tissues of this organ and compromising air circulation. The severe dehydration of the falcon reported in this study is more likely due to a decrease in food intake owing to its fractured left wing, which restricted its ability to search for food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, despite retrieving only two helminths, the peregrine falcon presented signs of respiratory illness including wheezing upon auscultation of the air sacs as well as thickening and opacity of the affected air sac. Veiga et al (2017) showed that adult Serratospiculum species can survive for many years within the air sacs causing alterations in the tissues of this organ and compromising air circulation. The severe dehydration of the falcon reported in this study is more likely due to a decrease in food intake owing to its fractured left wing, which restricted its ability to search for food.…”
Section: Discussionmentioning
confidence: 99%
“…Like other spirurids, Serratospiculum spp. are heteroxenous, using coprophagous beetles, grasshoppers, woodlice, and locusts as intermediate hosts and birds as a definitive host (Bain and Vassiliades, 1969;Veiga et al, 2017). The adult worms lay their embryonated eggs in the air sacs of birds, which are then passed through the lungs, and then coughed up and swallowed, eventually reaching the digestive system where they are eliminated via bird droppings.…”
Section: Serratospiculosis In a Wild Peregrine Falcon (Falco Peregrinus) From The Cerrado Region Minas Gerais Brazilmentioning
confidence: 99%
“…Serratospiculoides amaculata was first reported and sequenced in a parid host, the great tit Parus major , in Slovakia ( Dolinská et al, 2018 ; Königová et al, 2013 ). While previously only known to infect falcons ( Bain and Vassiliades, 1969 ; Schader and Baron, 2021 ; Van Wettere et al, 2018 ; Veiga et al, 2017 ), S. amaculata now appears to be expanding its hosts to passerines, and its geographic range, having recently been detected in great tits in southern Germany ( Abdu et al, 2022 ). Common amongst some passerines is the near identical genus Diplotriaena ( Seibert, 1944 ; Sonin, 1974 ), which has been discovered to infect blue tits Cyanistes caeruleus following a major mortality event in southern Germany ( Rentería-Solís et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most species of air sac nematodes belong to the genus Serratospiculum and Serratospiculoides (Honisch and Krone 2008). Infections in falcons (Family Falconidae, Genus Falco) appears to be common (Samour and Naldo 2001;Santoro et al 2016;Veiga et al 2017) with a high overall prevalence in this group. For example, Serratospiculum seurati occurs commonly in falcons in the Middle East, both in wild and captive birds (Al Timimi et al 2009).…”
mentioning
confidence: 99%
“…Reports on the occurrence of air sac nematodes in accipitrids are proportionally less common (Sterner and Espinosa 1988;Ackerman et al 1992;Taft et al 1993), suggesting air sac nematodes are less prevalent in this group. Recently, Samour and Naldo (2001), Tarello (2006), andVeiga et al (2017) reviewed the clinical, pathologic, and epizootiologic aspects of this parasitosis.…”
mentioning
confidence: 99%